Vertébrés (crocodilians, poisons) du Miocène marin de l’Algarve occidentale - Antunes, M. Telles (2008)
Karst fillings rich in fossils from carbonate series, Miocene in age, exposed on the coast of Algarve, yielded some thousands of teeth and other vertebrate remains. A crocodilian and more than fifty species of fishes (Selacians, Teleosteans) have been identified (see tableau 1). This fauna is consistent as a whole with a Burdigalian (maybe late) and/or Langhian age. It also indicates shallow waters, warmer than at present in the same region although not strictly tropical. This fauna shows more affinities with others of the same age from mediterranean region (i.e. Baleares) than with those from Lisbon.